Validation of the REVEAL Prognostic Models in Systemic Lupus Erythematosus-Associated Pulmonary Arterial Hypertension - Qu, Jingge; Li, Mengtao; Zeng, Xiaofeng; Zhang, Xiao; Wei, Wei; Zuo, Xiaoxia; Zhu, Ping; Ye, Shuang; Zhang, Wei; Zheng, Yi; Qi, Wufang; Li, Yang; et al. (Frontiers in Medicine, 2021)
No previous studies have investigated the predictive performance of the Registry to Evaluate Early and Long-term Pulmonary Arterial Hypertension Disease Management (REVEAL) prognostic equation and simplified risk score calculator in patients with systemic lupus erythematosus-associated pulmonary arterial hypertension (SLE-PAH). We aimed to validate these prediction tools in an external cohort of patients with SLE-PAH. In this study, the validation cohort consisted of patients with SLE-PAH registered in a prospective, multicenter, nationwide database between November 2006 and May2016. The follow-up of patients was censored at 1 year. Discrimination, calibration, model fit, and risk stratification of the REVEAL prognostic equation and simplified risk score calculator were validated. As a result, a total of 306 patients with SLE-PAH were included. The 1-year overall survival rate was 91.5%. The C-index of the prognostic equation was 0.736, demonstrating reasonably good discrimination, and it was greater than that for the simplified risk score calculator (0.710). The overall calibration slope was 0.83, and the Brier score was 0.079. The risk of renal insufficiency and World Health Organization Functional Class III (WHO FC III) were underestimated, and the risk assigned to a heart rate >92 bpm in the REVEAL prognostic models was not observed in our validation cohort. Both model discrimination and calibration were poor in the very high-risk group. In conclusion, the REVEAL models exhibit good discriminatory ability when predicting 1-year overall survival in patients with SLE-PAH. Findings from both models should be interpreted with caution in cases of renal insufficiency, WHO FC III, and heart rate >92 bpm.